URGENSI KAEDAH TAFSIR DALAM PENAFSIRAN AL-QUR’AN - Novizal Wendry (Universitas Islam Negeri Imam Bonjol Padang, 2016)
Qawâ`id al-tafsîr as a kind of `ulūm al-Qur’ân has a significant developments in this contemporary era. One of its supporting aspect is spirit and firmly of `ulūm al-Qur’ân s scholars’ in order to see Qur’anic meaning with linguistic approach. Qawâ`id al-tafsîr is general theories that become a standard by mufassir in order to understand the meanings of al-Qur’an and to know the way to use it. It is taken by induction from many quranic verses and exegeses of mufassir toward al-Qur’an, especially linguistic mufassir.